A study on the association of ACE i/D gene polymorphism, Obesity, Blood pressure and susceptibility of type 2 diabetes mellitus among the Kurmis of West Bengal, India. - Sarkar, Pranabesh; Chattrejee, Diptendu; Ratan Bandyopadhyay, Arup (Journal of Immunology and Geriatrics, 2016)
Earlier studies reported significant association of obesity, hypertension and Type2 Diabetes Mellitus (T2DM). Genetic and many disease-associated alleles have been identified through GWAS and applied to T2DM and indicated roles of renin-angiotensin system (RAS) in insulin signaling pathway and insulin resistance has been well documented. Angiotensin converting enzyme (ACE) gene catalyzes the conversion of angiotensin I to angiotensin II and also inactive the vasodilatation and hence renin-angiotensin system (RAS) in insulin signaling pathway and insulin resistance has been reported. To best of the knowledge we are reporting for the first time regarding association of ACE gene polymorphism with body composition, physiological and metabolic variables among any endogamous ethnic group (Kurmis) from of West Bengal, Eastern India. To achieve the purpose, total 197 (male 99 and female 98) randomly selected apparently healthy unrelated adult individuals of Kurmi population of Purulia District, West Bengal, India were incorporated in the present study. Anthropometric variables, physiological variables (blood pressure) and metabolic variables (PP blood sugar) have been collected using standard techniques. Extracted genomic DNA was PCR amplified and genotyped to understand ACE gene I/D polymorphism. The result demonstrated significant (p<0.05) sexual dimorphism in PBF. MAP and PP blood sugar found to be in normal range among the Kurmis. ACE gene polymorphism showed no deletion of the Kurmis and hence, only the prevalence of ACE II (insertion-Insertion) genotype has been noticed. The present study vindicated on the basis of body composition in terms of fat patterning, physiological and metabolic variables and ACE gene polymorphism that there is very low or no risk of T2DM among the Kurmis of West Bengal, India.
Keywords: ACE gene; obesity; blood pressure; Type 2 diabetes; Kurmi population